2014
DOI: 10.1890/13-0932.1
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradients in herbivory onOenothera biennisvary according to herbivore guild and specialization

Abstract: The latitudinal herbivory-defense hypothesis (LHDH) posits that herbivory and plant defenses increase toward lower latitudes. Recent studies provide contradictory evidence and suggest alternative explanations for biogeographic patterns in plant-herbivore interactions. Here we test the LHDH by sampling herbivory from multiple generalist and specialist insect herbivores over the entire latitudinal native range of the plant species Oenothera biennis L. (Onagraceae). We sampled 79 populations on a 168 north-south … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
97
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 50 publications
11
97
2
Order By: Relevance
“…We also detected some variation in the patterns of leaf herbivory along environmental gradients across feeding guilds. Differences in the patterns of herbivory among different guilds of herbivores have also been reported in studies conducted in temperate and tropical regions (Anstett et al, ; Novotny et al, ). However, there are also studies which reported similar patterns of herbivory by different feeding guilds along an elevation gradient (Garibaldi et al, ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We also detected some variation in the patterns of leaf herbivory along environmental gradients across feeding guilds. Differences in the patterns of herbivory among different guilds of herbivores have also been reported in studies conducted in temperate and tropical regions (Anstett et al, ; Novotny et al, ). However, there are also studies which reported similar patterns of herbivory by different feeding guilds along an elevation gradient (Garibaldi et al, ).…”
Section: Discussionmentioning
confidence: 62%
“…Evidence suggests that the monotonic pattern is often observed when herbivory is related to temperature and stable climates along an elevation gradient. However, alternative patterns occur particularly when factors such as herbivore feeding guilds (Anstett, Naujokaitis‐Lewis, & Johnson, ; Galmán et al, ), species and functional composition (Anstett et al, ), biogeographic zones (Kozlov, Lanta, Zverev, & Zvereva, ), scale effects (truncated vs. full‐scale elevation gradients) (Nogués‐Bravo, Araújo, Romdal, & Rahbek, ), shifts in vegetation types and position of more limiting conditions in relation to elevation (e.g. drought or arid conditions in lowlands) are taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…; Adams & Zhang ; Adams et al . ), mixed (Anstett, Naujokaitis‐Lewis & Johnson ; Kim ; Moreira et al . ) or no relationship between latitude and herbivory (Andrew & Hughes ; Sinclair & Hughes ; Feller et al .…”
Section: Introductionmentioning
confidence: 99%
“…The power and utility of this technique has been amply demonstrated by numerous recent studies. Some recent examples include: Anstett et al 2014, Baltensperger and Huettmann 2015, Baltensperger et al 2015, Barrios-Garcia et al 2014, Hernández et al 2007, Huber 2015, Senterre et al 2004.…”
Section: Introductionmentioning
confidence: 99%